Capability of Cellulolytic Degradation (BSD) Bacteria (CDB) to Remodel Organic Waste into Compost - Samah, Eri Samah; Misdawati, (Jurnal Online Pertanian Tropik, 2019)
Capability of Cellulolytic Degradation (BSD) Bacteria (CDB) to Remodel Organic Waste into Compost The purpose of this study was to obtain superior cellulolytic bacteria from acid soils as a starter for the degradation of organic waste in the city of Padang by testing the activity of cellulase enzymes. The method used in the factorial method is the Cellulolytic Degradation Bacteria factor with the Organic Waste of Padang City. This research was conducted at the Plant Physiology Laboratory and the Soil Science Laboratory, Faculty of Agriculture. The research activity was begun by isolating the bacteria from acid soil, followed by testing the enzyme activity of the specific medium of carboxyl methylcellulose (CMC) medium. Factorial Complete Random Design Method. The first factor was selected 3 isolates of cellulolytic bacteria, the second-factor main market organic waste at of Padang and was two treatments namely unstable sterile (A) and nonsterile (B). The research results obtained 6 isolates of cellulolytic bacteria with a clear zone index â‰¥ 2, namely Km25, Sr. 75, Jm, U-6, G-8, and Km 13, respectively 3.12; 3.04; 3.0; 2.04; 2.00, and 2.04, and used for composting organic waste 3 isolates of clear zone bacteria â‰¥ 3.0 isolates of KM25, Sr75, and JM respectively 3.12; 3.04; 3.01. Non-sterile organic waste is better than sterile due to the non-sterile, there is the help of battery change from the trash. Conclusion The best composting material is not sterilized, and better bacteria decompose the waste combined with the three isolates KM25, SR75, and JM.